2014
DOI: 10.3390/ani4040712
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Transfer from Breeding to Research Facility on the Welfare of Rats

Abstract: Simple SummaryThis study measured effects of transfer on body temperature, stress hormone levels, body weight, behavior and water and food intake in rats. Environmental temperature strongly affected body temperature of rats and needs to be controlled. Male rats need to habituate for at least one week, females for two weeks after transfer.AbstractTransfer from the breeding facility to a research facility is a stressful event for laboratory animals. Heat stress has been reported to constitute one of the major co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…The distance transported per se (Kalueff, 2016 ) is likely of less importance with regard to the animals used in Momeni et al ( 2015 ), considering that negligible effects were demonstrated in mice bred locally vs. shipped (Wahlsten et al, 2003 ). Moreover, the undisturbed acclimatization period of 2 weeks upon arrival is in line with recommendations for male rats (Arts et al, 2012 , 2014a , b ), also when transferred from normal to reversed light/dark cycle (Arts et al, 2016 ).…”
supporting
confidence: 69%
“…The distance transported per se (Kalueff, 2016 ) is likely of less importance with regard to the animals used in Momeni et al ( 2015 ), considering that negligible effects were demonstrated in mice bred locally vs. shipped (Wahlsten et al, 2003 ). Moreover, the undisturbed acclimatization period of 2 weeks upon arrival is in line with recommendations for male rats (Arts et al, 2012 , 2014a , b ), also when transferred from normal to reversed light/dark cycle (Arts et al, 2016 ).…”
supporting
confidence: 69%
“…Notably, the Harlan Laboratories at Horst (Netherlands) are located ~1500 km from Uppsala, compared to a 900-km distance to Taconic Farms at Ejby (Denmark) and nearly a 1700-km distance to the Charles River in Sulzfeld (Germany). The impact of transportation on psychological and physiological parameters in Wistar rats has recently been recognized (Arts et al, 2012 , 2014a , b ), raising the possibility that robust differences in transportation duration (~1700 vs. ~1500 vs. ~900 km) and, most likely, mode, packaging and shipment procedures, between the three suppliers could also contribute to overt behavioral differences reported by Momeni et al ( 2015 ). Although usually this technical information is not described in-depth in neurobehavioral papers, the study of Momeni et al ( 2015 ) suggests the opposite, indicating that vendor-related influences may indeed be critical in behavioral assays.…”
mentioning
confidence: 99%
“…Consequentially, research has shown changes in the transported animals’ physiological parameters such as heart rate, breathing rate, blood pressure, body temperature and hormone levels (Arts et al, 2014 ; Rumpel et al, 2019 ), based on their recent research, go on to offer a general guide that: At least seven days of acclimatization is recommended following transport between sites and at least three days between buildings on the same site [22]. However, depending on the severity and duration of the stress experienced and the parameter to be investigated, the period of acclimatization may take several weeks to normalize, as observed for blood pressure (three weeks) [23], as well as corticosterone and immune parameters (three weeks) [24] in BALB/c mice.…”
Section: Context: Regulation Scale Of Laboratory Mice Movement and So...mentioning
confidence: 99%